2011
DOI: 10.1186/2041-9139-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Heterochrony and developmental modularity of cranial osteogenesis in lipotyphlan mammals

Abstract: BackgroundHere we provide the most comprehensive study to date on the cranial ossification sequence in Lipotyphla, the group which includes shrews, moles and hedgehogs. This unique group, which encapsulates diverse ecological modes, such as terrestrial, subterranean, and aquatic lifestyles, is used to examine the evolutionary lability of cranial osteogenesis and to investigate the modularity of development.ResultsAn acceleration of developmental timing of the vomeronasal complex has occurred in the common ance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 69 publications
(133 reference statements)
3
62
1
Order By: Relevance
“…One explanation for this variability is that the selective forces acting upon the craniodental morphology of each sex may be different between populations. However, it should be noted that many craniodental traits are often associated with one another [11,18,19]. If quantitative aspects of such traits are significantly integrated in a likewise manner, the apparent sexual dimorphism observed in some traits might be a byproduct of true sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this variability is that the selective forces acting upon the craniodental morphology of each sex may be different between populations. However, it should be noted that many craniodental traits are often associated with one another [11,18,19]. If quantitative aspects of such traits are significantly integrated in a likewise manner, the apparent sexual dimorphism observed in some traits might be a byproduct of true sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…As a methodological problem, the stage resolution among the studied species has an important influence when reconstructing ancestral sequences and may disguise actual developmental patterns (discussed by Germain and Laurin, 2009;Werneburg andSánchez-Villagra, 2009, 2011;Koyabu et al, 2011;Laurin and Germain, 2011;Werneburg et al, 2013b). Small sample sizes for particular embryological ages inevitably provide reduced resolution for the timing of any given developmental event.…”
Section: Broad-scale Taxonomic Analysesmentioning
confidence: 97%
“…Although the onset of ossification only represents a minute excerpt of a long process of bone differentiation, recent comparative studies of the sequence of developmental events in skeleton formation have suggested general patterns of developmental similarity across a range of vertebrate groups (Sánchez-Villagra, 2002;Schoch, 2006;Maxwell, 2008;Weisbecker et al, 2008;Germain and Laurin, 2009;Weisbecker and Mitgutsch, 2010;Koyabu et al, 2011Koyabu et al, , 2014Werneburg and Sánchez-Villagra, 2015). As a rule of thumb, the earlier an element appears during development, the more prominent it becomes in the adult because it has more time to grow (Mehnert, 1897(Mehnert, , 1898Huxley, 1932;Sánchez-Villagra et al, 2008;Maxwell, 2009;Maxwell and Larsson, 2009;Werneburg and Sánchez-Villagra, 2015).…”
Section: The 'Early Equals Important' Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Many layers of developmental patterning may obscure each other, termed the "palimpsest" problem (42). Indeed, there seems to be little to no relationship between cranial phenotypic modules and coordination of skeletal heterochronies (25,(43)(44)(45), unlike in the postcranial skeleton. Nonetheless, quantitative approaches can estimate the developmental contribution to phenotypic integration in fossil taxa, even without identifying a specific developmental driver, by measuring fluctuating asymmetry (FA).…”
Section: Significancementioning
confidence: 99%